Exploring the Attitude of Chinese Self-drive Tourists Towards Driving Safety in New Zealand - Li, Chenxi (Auckland University of Technology, 2020)
Road safety is a global issue that has been given attention in many countries. In tourist destinations, a high rate of car accidents can negatively influence the tourism market image. Self-drive tourism has become popular in China in the past decade, and along with the rise of the self-drive travelling trend, New Zealand has become a popular destination, attracting thousands of Chinese self-drive tourists. However, the number of car crashes of Chinese self-drive tourists has gradually increased, which not only endangers tourists and locals but also impacts on New Zealand’s image in the Chinese market. New Zealand official reports show that international drivers from right-side driving countries are the main at-fault group in international car accidents due to their driving on the wrong side of the road and not obeying ‘Give Way’ rules (Ministry of Transport, 2017). China is the second-largest inbound tourism market of New Zealand (Statistics New Zealand, 2018), brings significant economic benefits, and promotes the development of tourism. However, the number of Chinese visitors in fatal or injury crashes in New Zealand ranked third of international visitors’ car crashes, which was over 100 drivers in 2016 (Ministry of Transport, 2017), negatively affecting word-of-mouth advertising of New Zealand tourism in China. Therefore, understanding Chinese self-drive tourists’ attitudes towards road safety in New Zealand is important. Netnography is employed in this study to identify the themes and patterns in online reviews posted by Chinese self-drive tourists who visited New Zealand. The results showed most self-drive tourists were young or middle aged, and travelling with friends. A lack of tourism infrastructure, poor car condition, and bad weather, were the main reasons given for road accidents. The findings of this qualitative study have important implications for the New Zealand tourism industry and Government, in managing the road safety of international tourists.
Keywords: Chinese tourist; Self-drive tours; Road safety; New Zealand